2016
DOI: 10.3390/ma9070547
|View full text |Cite
|
Sign up to set email alerts
|

Repair Bond Strength of Aged Resin Composite after Different Surface and Bonding Treatments

Abstract: The aim of this study was to compare the effect of different mechanical surface treatments and chemical bonding protocols on the tensile bond strength (TBS) of aged composite. Bar specimens were produced using a nanohybrid resin composite and aged in distilled water for 30 days. Different surface treatments (diamond bur, phosphoric acid, silane, and sandblasting with Al2O3 or CoJet Sand), as well as bonding protocols (Primer/Adhesive) were used prior to application of the repair composite. TBS of the specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 46 publications
6
53
1
5
Order By: Relevance
“…There are conflicting results between the studies in terms of contribution to bond strength. Although some studies indicated that they increase (39) or decrease (36,40) bonding strength, some studies have not found any significant effect (26,41). In the present study, while acid treatment with the bonding agent decreased the bonding strength between the composites, it improved the bonding strength between the RMGIC and the RBC.…”
Section: Discussioncontrasting
confidence: 64%
“…There are conflicting results between the studies in terms of contribution to bond strength. Although some studies indicated that they increase (39) or decrease (36,40) bonding strength, some studies have not found any significant effect (26,41). In the present study, while acid treatment with the bonding agent decreased the bonding strength between the composites, it improved the bonding strength between the RMGIC and the RBC.…”
Section: Discussioncontrasting
confidence: 64%
“…Composite repair often presents a different challenge, especially because the surface of aged composites lacks any unreacted double bonds available for bonding to the new composite 10,11) . Although there is no laboratorial aging protocol considered as gold standard that simulates this phenomenon, some authors have followed the principle that 10,000 cycles correspond to one year of physiological aging in the oral cavity 8) , what would be enough to promote a considerable increase in the double bond conversion of composite materials.…”
Section: Discussionmentioning
confidence: 99%
“…Although phosphoric acid is not capable of modifying the surface topography, 11 it has a cleansing effect, eliminates the surface debris and enhances surface energy and wettability of the surface. 11,36 The subsequent application of a silane coupling agent might have improved the union between the surface of the hybrid ceramic and the resin cement. It can be assumed that adequate surface activation was provided through silanization and chemical interaction rather than micromechanical bonding.…”
Section: Discussionmentioning
confidence: 99%